Compatibility of Composite Biomaterials in Sports Injury Repair. (20th August 2021) - Xing, Mo
Abstract : With the rapid development of sports, sports injuries have become an inevitable problem in sports. Repairing sports injuries has always been the focus of attention in the field of sports and medicine. The wide application of biomedical materials leads to the innovation and development of medical technology. It is of great significance to use them to repair sports injuries, but the current research results are not ideal. In this paper, the biocompatibility of composite biomaterials used to repair sports injuries was studied. First, the rat bone marrow mesenchymal stem cells were cultured to prepare a cell suspension. Then, the tricalcium phosphate-gelatin composite scaffold material and the collagen material were scraped into powder to make the material extract, which are, respectively, the experimental group and the control group. An apoptosis detection kit and a flow cytometer were used to detect apoptosis rate and survival rate of all samples, and a CKK-8 kit was used to detect cytotoxicity and calculate cell proliferation activity. The absorbance value was read with a microplate reader, and the coagulation performance and hemolysis rate of different groups were calculated. The experimental results showed that the cell survival rate of the experimental group was 91.41%, the early apoptosis rate was 2.81%, the stem cell proliferation activity was 0.83, and the anticoagulant performance and hemolysis rate were 64.8% and 0.28%, respectively. This indicates that although the anticoagulant performance of the tricalcium phosphate-gelatin composite scaffold is weak, its cell proliferation activity is strong, which is more suitable for cell adhesion and proliferation, and the cell apoptosis and hemolysis rate are lower. Therefore, it has better biocompatibility than a single collagen material.